Studi Literatur: Standar Penerapan Objek Pajak Fiskal Pada Era 4.0 Di Indonesia - -, Reski; Mariati Tahir; Haryanti; Hidayatullah; Ahmad Imam Meilana (Indonesian Journal of Research in Economy, 2022)
The Indonesian government needs to implement a tax system that is efficient and in accordance with regulations for entrepreneurs, so that the government can meet the needs of the Indonesian people. One strategy that can be carried out by taxpayers, both individuals and entities, is tax planning to reduce the tax obligations that must be paid. The phenomenon of the Industrial Revolution era 4.0, which is characterized by the integration of automation technology, is the focus of this research. The research method used is qualitative concept analysis using secondary data, including financial accounting standards, tax regulations, agency annual reports, scientific journals and other relevant literature.